PIEZOELECTRIC COEFFICIENT PROPERTIES OF A FLEXIBLE PZT/UPE/C COMPOSITE - Noori, Z T Mohammed; Noori, F Mohammed (Al-Nahrain Journal of Science, 2010)
A flexible piezoelectric composite, made from Lead Zirconate Titanate(PZT) powder andUnsaturated polyester (UPE) resin, was doped with small amount of carbon semiconductor powder.The piezoelectric strain coefficient (d33) and the dielectric behavior have been studied for thisceramic/polymer composite. The dielectric constant processes of the composite were observed to bedominated by those of undoped ceramic- polymer. The practical results of PZT/UPE/C with ratio49/50/1 adding a semiconductor phase in the composite showed piezoelectric strain coefficient canbe controlled and a continuous electric flux path could be created between the PZT grains. Thiscomposite may be poled at low voltage and in shorter time compared with composites without aconductive phase.